2013
DOI: 10.1186/1748-717x-8-5
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective feasibility study of simultaneous integrated boost in cervical cancer using tomotherapy: the impact of organ motion and tumor regression

Abstract: BackgroundWhole pelvis intensity modulated radiotherapy (IMRT) is increasingly being used to treat cervical cancer aiming to reduce side effects. Encouraged by this, some groups have proposed the use of simultaneous integrated boost (SIB) to target the tumor, either to get a higher tumoricidal effect or to replace brachytherapy. Nevertheless, physiological organ movement and rapid tumor regression throughout treatment might substantially reduce any benefit of this approach.PurposeTo evaluate the clinical targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 32 publications
2
13
0
1
Order By: Relevance
“…The reduction in treatment time is of particular clinical significance as previous work from our institution (12) and others (13‐15) has demonstrated that protracted treatment duration compromises local control in this patient population. Because nodal targets are not expected to be greatly affected by organ motion (26) and because modest doses are indicated for nodal targets by NCCN guidelines, this is an ideal scenario in which to harness the power of SIB planning. To our knowledge, this is the first study to demonstrate the advantages of SIB over sIMRT for boosting PET‐avid nodal targets in locally advanced cervical cancer in a systematic manner.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The reduction in treatment time is of particular clinical significance as previous work from our institution (12) and others (13‐15) has demonstrated that protracted treatment duration compromises local control in this patient population. Because nodal targets are not expected to be greatly affected by organ motion (26) and because modest doses are indicated for nodal targets by NCCN guidelines, this is an ideal scenario in which to harness the power of SIB planning. To our knowledge, this is the first study to demonstrate the advantages of SIB over sIMRT for boosting PET‐avid nodal targets in locally advanced cervical cancer in a systematic manner.…”
Section: Discussionsupporting
confidence: 68%
“…Organ motion and CTV regression during treatment are also important factors to consider when prescribing higher doses to a boost volume. Herrera et al (26) used weekly on‐board megavoltage CT to track target volume motion and regression during six weeks of treatment. The pelvic CTV volume decreased over six weeks for all patients, but did not result in underdosing except in the two patients whose uteri became retroverted during the course of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The dosimetric effects of anatomical changes will be greater for IMPT than VMAT as proton stopping power is more sensitive to tissue changes than the corresponding photon interaction coefficients. These effects have previously been investigated for standard and dose escalated intensity modulated radiotherapy (IMRT) of cervix cancer [ 25 , 26 ] and for IMPT with a SIB for prostate cancer [ 27 ]. Herrera et al [ 26 ] analyzed dose escalation of a central target volume including the uterus over 28 fractions using deformable registration of weekly CBCT images.…”
Section: Discussionmentioning
confidence: 99%
“…These effects have previously been investigated for standard and dose escalated intensity modulated radiotherapy (IMRT) of cervix cancer [ 25 , 26 ] and for IMPT with a SIB for prostate cancer [ 27 ]. Herrera et al [ 26 ] analyzed dose escalation of a central target volume including the uterus over 28 fractions using deformable registration of weekly CBCT images. They found, compared to planned values, overdosage of adjacent OARs correlating with tumour shrinkage and recommended frequent plan adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…This approach has its advantages compared to sequential dosage increment, namely: the possibility to deliver different fraction doses to different volumes, shorten overall treatment time (OTT), and guarantee better coverage of Gross Tumor Volume (GTV) with non-target tissue sparing. SIB use has also been investigated in diseases other than anal canal cancer, such as head and neck cancer and cervical cancer, and where it has been demonstrated to be feasible and act to reduce acute toxicity [6][7][8] . Here we present the results of a study carried out with an intensified radiotherapy regimen associated with chemotherapy that was applied in order to improve oncologic efficacy and reduce overall acute toxicity in patients with squamous cell carcinoma of the anal canal treated at our center.…”
Section: Introductionmentioning
confidence: 99%